Unsettled Rights: Afro-descendant recognition and ex-situ titling in Colombia. (June 2022) - Hougaard, Inge-Merete
Abstract: Ethnic recognition and collective titling have since the second half of the 20th century been promoted as ways of compensating for historical injustices and countering the destructive effects of capitalist development. While holding promise of autonomy, territorial rights, and resource control, they have also been seen as political technologies governing, spatially tying identities to place, and incorporating new areas into capital market relations. This paper draws on and contributes to these debates by exploring how the Colombian legislation for Afro-descendants ethnic recognition and collective titling is understood, employed and 'reworked' from below as well as from above. Drawing on ethnographic fieldwork, interviews, and document analysis, the paper follows the case of an Afro-descendant sand-extracting community in the Cauca Valley Region, Colombia. Threatened by a competing mining claim, the villagers seek to gain ethnic recognition among other things to secure rights and control mining resources. In the process, the villagers are offered a land plot away from where they live and work to title as their collective territory; a mechanism that I term 'ex-situ titling'. As the villagers have no prior relation to the land, nor intend to resettle there, I argue that the ex-situ land titling only serves as a procedural step in the process of ethnic recognition, which, nevertheless, contributes to the uncertainty and incertitude around the villagers' ethnic rights and resource control. Highlights: Ethnic recognition for Afro-descendants in Colombia is premised on collective title. Legislation for Afro-descendant ethnic recognition is reworked from above and below. Reworking results in 'ex-situ titling' as a new form of collective titling. Ex-situ titling implies titling land outside villagers' residence and production. Potential implications of ex-situ titling on resource rights are discussed.